The Gut Microbiome as a Mechanistic Link Between the Planetary Health Diet and Healthy Aging - Tamás Jarecsny; Andrea Lehoczki; Tamás Csípő; Vince Fazekas-Pongor; Noémi Mózes; Boglárka Csík; Virág Zábó; Ágnes Lipécz; Dorottya Nyáry; Mónika Fekete (Nutrients, 2026)
Population aging, the rising burden of chronic non-communicable diseases, and environmental degradation are increasingly recognized as interconnected global challenges, underscoring the need for integrated strategies that simultaneously promote human and planetary health. The Planetary Health Diet (PHD), originally proposed to address these challenges, has emerged as a promising dietary framework for supporting healthy aging. Although its health benefits are increasingly supported by epidemiological and clinical evidence, the biological mechanisms underlying these effects remain incompletely understood. This narrative review synthesizes evidence on the interplay among the PHD, the gut microbiome, and biological aging, with emphasis on microbiome-mediated pathways connecting sustainable nutrition with healthspan. Adherence to PHD-consistent dietary patterns is associated with greater microbial diversity and functional capacity, increased production of bioactive microbial metabolites, and more favorable intestinal barrier, immune, and metabolic profiles. These adaptations may modulate several hallmarks of aging and contribute to the preservation of physiological resilience. Evidence from prospective cohort studies, randomized controlled trials, and systematic reviews further indicates that dietary patterns consistent with the PHD are associated with lower risks of cardiometabolic diseases, frailty, cognitive decline, and premature mortality. By integrating findings from nutritional science, microbiome research, geroscience, and public health, this review positions the gut microbiome as an important, although not exclusive, biological interface through which sustainable dietary patterns may support healthspan while contributing to environmental sustainability.